The current development of the cheese market in Ukraine - Volkova, I. D. (ТДАТУ, 2019)
Agriculture is the backbone of Ukraine's economy, so it is necessary to regularly support and improve agricultural enterprises, enabling them to develop steadily and be globally competitive.
Keywords: economy; dairy market; cheese market; imports of cheeses